Effects of Multi-Component Mixtures from Sewage Treatment Plant Effluent on Common Carp (Cyprinus carpio) under Fully Realistic Condition - Giang, Pham Thai; Burkina, Viktoriia; Sakalli, Sidika; Schmidt-Posthaus, Heike; Rasmussen, Martin Krøyer; Randak, Tomas; Grabic, Roman; Grabicova, Katerina; Fedorova, Ganna; Koba, Olga; Golovko, Oksana; Turek, Jan; et al. (Environmental management, 2019)
This study characterized changes in biomarker responses in common carp (Cyprinus carpio) upon exposure to effluent water discharged from a sewage treatment plant (STP) under real conditions. Fish were exposed to contamination in Cezarka pond, which receives all of its water input from the STP in the town of Vodnany, Czech Republic. Five sampling events were performed at day 0, 30, 90, 180, and 360 starting in April 2015. In total, 62 pharmaceutical and personal care products (PPCPs) were detected in the polar organic chemical integrative sampler. Compared to a control pond, the total concentration of PPCPs was 45, 16, 7, and 7 times higher in Cezarka pond at day 30, 90, 180, and 360, respectively. The result of oxidative stress and antioxidant enzyme biomarkers indicated alterations in the liver and intestine tissues of fish from Cezarka pond at day 30 and 360, respectively. High plasma vitellogenin levels were observed in both exposed females (180 and 360 days) and males (360 days) compared with their respective controls. However, only exposed female fish had higher vitellogenin mRNA expression than the control fish in these periods. Exposed female fish showed irregular structure of the ovary with scattered oocytes, which further developed to a vitellogenic stage at day 360. Low white blood cell levels were indicated in all exposed fish. Despite numerous alterations in exposed fish, favorable ecological conditions including high availability of food resulted in a better overall condition of the exposed fish after 1 year of exposure compared to the controls.
Keywords: Integrate biomarker response; Male; Carps; Female; Vitellogenins; Biological effects; chemické látky znečišťující vodu; kapři; ženské pohlaví; Sewage; Endocrine disruption; odpadní vody; mužské pohlaví; Animals; Water Pollutants, Chemical; zvířata; vitelogeniny; Biological pond